FORMATION OF DIDACTIC CULTURE OF FUTURE HISTORY TEACHERS - Shertaylakova, Gulnoza (Журнал иностранных языков и лингвистики, 2023)
Didactic culture plays a significant role in enabling effective teaching and learning of any subject. It encompasses the methods, procedures, tools, and resources used by educators to enhance students’ understanding of a subject. In the field of history, the formation of didactic culture among future teachers is essential to ensure that history is taught in an engaging and relevant way to younger generations. The subject of history is not only about learning about the past but also about developing critical thinking skills, understanding the present, and shaping the future. Hence, it is crucial that future history teachers are adequately equipped with the necessary didactic skills and knowledge to effectively address these goals. This article delineates the formation of didactic culture among future history teachers and discusses the key factors that contribute to it.